Bernhard Lichtenberg: Roman Catholic priest and martyr of the Nazi regime - Gaydosh, Brenda L. (Lexington Books, 2017)
From childhood to priesthood (1875=1899) -- Expanding the Catholic presence in Berlin (1900=1918) -- The Weimar years (1919-1933) -- Catholic accommodation and resistance (1933=1935) -- Nazi thrust and Catholic parry (1936=1939) -- The Nazi regime raises the stakes (1939=1941) -- In Nazi hands (1941=1942) -- Memory and beatification